Pengaruh Budaya Organisasi terhadap Kompetensi Pustakawan (Studi Kasus pada Universitas Islam Indonesia Yogyakarta) - Sungadi Sungadi (Institut Agama Islam Negeri Salatiga, 2018)
The problem faced by the Library of Islamic University of Indonesia (UII) is still 70.37%of librarians who have Diploma and Senior High School, so it is not in accordancewith the existing standards, that is the qualification of university librarians withminimum education of Bachelor (S1) in Library Science. The purpose of this study isto determine the effect of organizational culture on the competence of UII librariansin living their profession. The subject of this research is UII Librarian as many as 27people spread in several places, among others: in Directorate of UII Library, Faculty ofEconomics UII and Faculty of Law UII. During this time the librarian is still havingdifficulty in his career as a librarian, it is evident that almost every semester there aresome librarians who get warning letter from UII leaders related to their obligation toapply DUPAK (List of Proposal of Credit Rate Submission). The research is intendedto know the role of UII Library’s organizational culture towards the development oflibrarian competence of UII. The results showed that the level of organizational cultureUII Library and the level of competence Librarian UII perceived respondents in veryhigh category with the respective perceptions of 81.76 and 84.25. There is a positiveinfluence between organizational culture on the competence of Librarian UII withsignificance value 0.014 0.05 (0.014) smaller than 0.05). While the level of correlationbetween variables X with variable Y there is influence of 47.8% (0.478), wherethe value is in the classification is.